Ocena atrakcyjności turystycznej euroregionu Neisse-Nisa-Nysa - Januszewska, Małgorzata; Przeorek-Smyka, Renata (Neisse-Nisa-Nysa Euroregion Tourist Appeal Assessment, 2005)
The article deals with the problem of geographic space tourist appeal assessment. It presents the review of research methods applied in the assessment of this phenomenon extend, ąnd the role which may be assigned to correct identification of its geographic space diversification. The authors also present an evaluation of the three parts' tourist appeal as well as the advantages of the selected districts included in the Neisse-Nisa-Nysa Euroregion. They have also verified the obtained research results and compared them with the actual choices of tourists, which are reflected, among others, in the tourist movement taking place in the Euroregion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 41-55